2013
DOI: 10.1186/2193-1801-2-541
|View full text |Cite
|
Sign up to set email alerts
|

Emblica officinalis Garten fruits extract ameliorates reproductive injury and oxidative testicular toxicity induced by chlorpyrifos in male rats

Abstract: Organophosphate pesticides have destroying properties on male reproduction and chlorpyrifos adversely affects the male reproductive system. Emblica offcinalis Garten plays a vital role to challenge many diseases in human body. We investigated the induction of oxidative stress in the male reproductive system of adult rats (Wistar Strain) exposed to widely used organophosphate pesticide, Chlorpyrifos, and tried to establish the ameliorative properties of Emblica officinalis Garten with respect to reproductive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
5
20
0
Order By: Relevance
“…In agreement with previous studies, our histopathological examination of the testicular tissue revealed significant decline in the number of spermatogenic cells, Sertoli cells and inter‐tubular blood cells in CPF‐exposed groups (Dutta & Sahu, ; Elsharkawy et al, ; Mandal & Das, ; Mosbah et al, ; Sai et al, ). Among these cells, the mean spermatocyte and spermatid counts were significantly increased by some, and not all, treatment regimens in exercise‐trained groups when compared with the similarly treated sedentary animals (Figure e,f).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous studies, our histopathological examination of the testicular tissue revealed significant decline in the number of spermatogenic cells, Sertoli cells and inter‐tubular blood cells in CPF‐exposed groups (Dutta & Sahu, ; Elsharkawy et al, ; Mandal & Das, ; Mosbah et al, ; Sai et al, ). Among these cells, the mean spermatocyte and spermatid counts were significantly increased by some, and not all, treatment regimens in exercise‐trained groups when compared with the similarly treated sedentary animals (Figure e,f).…”
Section: Discussionsupporting
confidence: 92%
“…Some previous research works have shown that CPF administration leads to drastic histo‐morphologic changes in the testes of animal models, such as testicular atrophy, shrinkage of the seminiferous tubules, tubular diameter reduction and degenerative changes in the germinal epithelium (Dutta & Sahu, ; Elsharkawy, Yahia, & El‐Nisr, ; Farag et al, ; Mosbah, Yousef, Maranghi, & Mantovani, ). However, other studies have failed to detect some or all of these damages (Joshi et al, ; Kheradmandi, Jorsaraei, Feizi, Moghadamnia, & Neamati, ; Sai et al, ; Wen, Wei, & Pan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to Judo 40 led to impaired sperm motility and nuclear integrity [11]. Hence, the fertilization capabilities of sperm in the present study were significantly reduced because of spermatozoa movement dysfunction and a decrease in sperm DNA integrity, and this is evident from the reduction in pregnancy indices [71].…”
Section: Discussionmentioning
confidence: 58%
“…Progressive motility of spermatozoa and nuclear integrity is extremely important for successful fertilization [67]. Increased head abnormalities [68,69] and impaired sperm motility [70] leads to a reduction in fertilizing ability [71,72]. Exposure to Judo 40 led to impaired sperm motility and nuclear integrity [11].…”
Section: Discussionmentioning
confidence: 99%
“…Ameliorative efficacy of E. officinalis against chlorpyrifos and arsenic has also been demonstrated in animal models (Dutta & Sahu, ; Singh et al, ). Thus, it can be concluded from the present findings that MG adversely affects fish even at sublethal concentration and the negative impact of the dye can be reversed by diet supplementation of E. officinalis in C. carpio, thereby proving beneficial in aquaculture.…”
Section: Discussionmentioning
confidence: 99%